Socio-economic impact of microfinance in Nepal - Paudel, Narayan Prasad (Journal of Management and Development Studies, 2013)
The microfinance institutions (MFIs) in Nepal are constrained in capacity of key technical areas essential to rural finance operations such as accounting, auditing, strategic planning, financial analysis, and portfolio management. This lack significantly limits their potential to expand their client base and outreach to poor households. The number of MFIs with private sector's participation is expanding significantly. The overall impression of microfinance performance indicates that the microfinance clients, the loan portfolio outstanding, and savings are in increasing trend. Despite these efforts, the level of poverty remains unchanged across the rural households. As a measure of effect of microfinance, with the rise in membership duration, cooking fuel status of the clients is yet to be improved. The current monthly income of control group households is in declining trend at present. The rate of increase in monthly income of experimental group is quite high for the majority of the respondents. The household food sufficiency from household production is more pronounced in experimental group than in the control group. The contribution of other incomes in determining the total income of households is more significant in comparison to agricultural and farm related income raise through the microcredit facilities. The status of female child enrollment in private school has significantly increased irrespective of the level of earning of households.